EVALUATION OF ADIWIYATA PROGRAMS - Neneng KOMARIAH (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
This research was conducted to evaluate the effectiveness of the Adiwiyata program from the analysis of needs, objectives and indicators for program implementation, competence of teachers and students, the availability of infrastructure, implementation of the curriculum, the implementation of Adiwiyata program activities, and the results of the Adiwiyata program implementation related to attitudes and behavior of school members towards environmental awareness. This type of research is evaluative research with a qualitative approach. Data collection was carried out using interview, observation and documentation techniques. The results showed that the analysis of program needs was based on recommendations from the Tangerang City Environmental Office (DLH), as well as to facilitate a clean culture that has long been implemented by schools. The objectives of the program in general have been implemented effectively but the aim of providing skills to students in processing waste has not been going well. The supporting infrastructure for the Adiwiyata program is quite complete, but the fish pond and compost house are in poor condition. The curriculum on the environment has been integrated into the KTSP and the 2013 Curriculum but the implementation in intracurricular and extracurricular activities has not been effective. More than 70% of teachers have not inserted environmental material into the syllabus and lesson plans so that learning has not been effective. Clean Thursday, class pickets, plant care, community service and environmental hygiene competitions are environmental activities held by schools and run quite effectively. School residents are more concerned about the condition of the surrounding environment